A curve tracing algorithm using level set based affine transform - Lam, B.S.Y.; Yan, H. (Pattern recognition letters, 2007)
Extracting centrelines from an unordered data set is an important problem in image processing and pattern recognition. The key strategy of existing methods is to find a curve placed at the middle of the data points. However, if the data set contains noise, these algorithms will converge to a local minimum. In this paper, we propose a new technique, which combines the level set and affine transform methods. In this approach, the user-defined initial curve is driven towards the object data. Experimental results show that the proposed method can enhance the performance of a class of curve extraction algorithms effectively.